Isolation and characterization of an ammonium-oxidizing iron reducer: Acidimicrobiaceae sp. A6 - Huang, Shan; Jaffé, Peter R. (PLOS ONE, 2018)
Acidimicrobiaceae sp. A6 (ATCC, PTA-122488), a strain that has been previously reported to play a key role in the oxidation of ammonium (NH4+) under iron reducing conditions, has now been isolated from riparian wetland soils in New Jersey, USA. Incubations of this strain in a medium containing ferrihydrite as the ferric iron [Fe(III)] source, CO2 as the carbon source, under room temperature, and a pH of 4.5, resulted in 52% of NH4+ removal over a 20-day incubation period, while reducing Fe(III) in the expected stoichiometric ratio when NH4+ was oxidized to nitrite with Fe(III) as the electron acceptor. This study demonstrates that this new isolated strain is capable of oxidizing NH4+ while reducing iron under anaerobic conditions.